Influence of the method of conservation of lucerne on ruminal degradability. II. Nitrogen - Andueza D.; Muñoz F.; Pueyo J.; Delgado I.; Roza B. de la (Quality in lucerne and medics for animal production, 2001)
An experiment was carried out to evaluate the rumen degradability of the nitrogen of lucerne preserved as hay or dehydrated. Samples from three alternate cuts (spring, summer and autumn) at two phenological stages were taken from a lucerne plot located at Bujaraloz (Zaragoza) in 1998. The technique of nylon bags was used to determine the kinetics of nitrogen degradation. The fractions soluble (A), insoluble potentially degradable (B) and potentially degradable (A + B), the fractional degradation rate of the slowly degradable fraction (C) and the effective degradability (ED) were estimated according to the equation obtained by Orskov and McDonald, (1979). Significant differences were obtained among cuts and conservation methods for A, B, A plus B and ED. The interactions conservation method ¥ cut and conservation method ¥ phenological stage were significant for A, A plus B and ED. In general, forage preserved as dehydrated showed lower values of ED than hay forage.
14. Réunion Eucarpia du Groupe Medicago spp., 2001/09/12-15, Zaragoza and Lleida (Spain)